A multi‐objective model for publicly funded festival planning - Almeida, Luís Alçada (2024)
This article proposes a multi-objective mixed-integer linear programming model to assist event managers in obtaining and evaluating non-dominated solutions to the problem of selecting a daily lineup of shows and activities for a festival – be it cultural, sports, ceremonial or any other kind. The model, which is especially adequate for designing festivals with public funding, has five objectives, relating to financial, logistical and how renowned the festival artists or acts are. It includes support for multiple days, multiple stages and differ- ent types of shows, all subject to constraints imposed by the intrinsic nature of the festival itself. The output of the model is a set of optimized daily lineups for the activities that constitute the festival, each correspond- ing to a particular compromise between the five objectives. The approach is demonstrated with a case study for a 5-day festival, for which non-dominated solutions are derived, presented and discussed. Results show that the model can provide a good variety of solutions while ensuring the persistence of the more desirable shows. The model is a novel decision support tool to assist in designing festival lineups that provide optimal audience experience, a key factor in attracting spectators, tourists and increasing comeback value.